The role of multimedia in surgical skills training and assessment. Issue 3 (June 2016) - Shariff, Umar; Seretis, Charalampos; Lee, Doreen; Balasubramanian, Saba P.
Abstract: Introduction: Multimedia is an educational resource that can be used to supplement surgical skills training. The aim of this review was to determine the role of multimedia in surgical training and assessment by performing a systematic review of the literature. Methods: A systematic review for published articles was conducted on the following databases: PubMed/MEDLINE (1992 to November 2014), SCOPUS (1992 to November 2014) and EMBASE (1992 to November 2014). For each study the educational content, study design, surgical skill assessed and outcomes were recorded. A standard data extraction form was created to ensure systematic retrieval of relevant information. Results: 21 studies were included; 14 randomized controlled trials (RCTs) and 7 non-randomized controlled trials (Non-RCTs). Technical skills were assessed in 7 RCTs and 3 non-RCTs; cognitive skills were assessed in 9 RCTs and 4 non-RCTs. In controlled studies, multimedia was associated with significant improvement in technical skills (4 studies; 4 RCTs) and cognitive skills (7 studies; 6 RCTs). In two studies multimedia was inferior in comparison to conventional teaching. Evaluation of multimedia (9 studies) demonstrated strongly favourable results. Conclusions: This review suggests that multimedia effectively facilitates both technical and cognitive skills acquisition and is well accepted as an educational resource.